Travail enseignant et transmission scolaire - Bernard Rey (Nantes Université, 2011)
In this article, we suggest that one cannot analyse teaching activities without referring to the anthropological form of transmission in which it is realized. Indeed, in modern societies the transmission of societal practices from one generation to another is mainly organised under a didactised form ("une forme didactisée"). This means that these practices are not transmitted through the action and the ordinary conditions of their realisation, but in a secluded place, such as a school, and through speech. We reveal how speech tends to take a textual form, and yet the access to the text constitutes a major difficulty for students because it imposes a way of giving meaning to the utterance which is unusual or even unknown to them. Therefore, the teacher's activities consist in finding ways to resolve or to sidestep this difficulty. However, it turns out that each of these solutions, while partially solving a problem, genders new ones, which makes the work of teachers ceaselessly theatrical.